Analysis of the survival of technology-based companies linked to business incubators - de Oliveira Haase, Mariana Aparecida; de Faria, Adriana Ferreira; Santos Tupy, Igor (Innovation (North Sydney), 2025)
Technology-Based Enterprises (TBE) contribute to the economic development of nations through the diffusion of knowledge and innovation, thus being important for the economic growth and competitiveness of territo-ries and countries. Studies point out the difficulties in creating EBTs as well as the high mortality rate. Thus, this study aimed at analysing the survival of incubated and graduated EBTs linked to business incubators in the state of Minas Gerais, Brazil, considering the explanatory variables at the company, incubator, and municipality levels. Non-parametric and semi-parametric survival analysis statistical methods were used to, first, perform a descriptive analysis of survival characteristics and, second, evaluate the relationship of explanatory variables with survival time. A sample of 603 companies was used, obtained from the InovaData-MG platform, with a record of being active or inactive from January 1990 to December 2019, according to the Brazil-ian IRS website. The results pointed out that when disengaging from incuba-tors, graduated companies are subject to a higher risk of failure, and that in-cubated ventures that also went through an acceleration programme have a higher chance of survival. Failure rates showed a non-linear relationship with firm age. Firm-specific, microeconomic, and industry specifications have important implications for the survival of the studied EBTs. This study used a new data set and a statistical technique not usually employed, which allowed us to offer an important contribution to the prediction of the mortality of EBTs, helping the formulation of more assertive public policies for the growth and development of these companies.